"Flying Spark of Fire": Thinking (and) Action in Hannah Arendt. (1st October 2017) - Trimçev, Eno
Abstract : This article rethinks the space between the ontological and historical registers of Hannah Arendt's thought. In a first step, the article moves against Arendt by arguing that her ontological analytic of new beginnings cannot support an account of politics. In a second step, the article moves against Arendt's intentions but within her thought to undermine her divide between action and thinking by understanding both as instances of human experience. Finally, the article moves with Arendt to recover a language of experience whose terms gain meaning only in relation to one another for they have neither a strictly universal nor a strictly particular character. As an articulation, this language interweaves the creative insights of the ontological register into historical experiences thus remaining loyal to the Arendtian project.